Rancangan UI/UX Animal Shelter Dengan Menggunakan Design Thinking - Wulandari, Selvi Putri; Fahry, Rizky; Suswanti, Oktaviani E. P.; Arman, Molavi (Universitas Multi Data Palembang, 2024)
Animal Shelter is a platform used to report abandoned animals and also adopt animals at existing shelters with the aim of making it easier for users to report abandoned animals to shelters and also adopt animals. Animal shelters exist because of public complaints regarding the difficulty of finding shelters to report abandoned animals and adopt animals. The method used in this design is the Design Thinking Method, where this method consists of 5 stages, namely empathize, define, ideate, prototype, and testing. It is hoped that animal shelters can increase public awareness of abandoned animals and provide a good experience for users while using the application, by making it easier to access animal reporting and animal adoption at existing shelters